The upper-airway microbiota and loss of asthma control among asthmatic children - Yanjiao Zhou (Nature Portfolio, 2019)
How the airway microbiome influences asthma pathophysiology remains unclear. Here, the authors analyse nasal samples of cohort of school-age children with persistent asthma and find that the microbiota’s patterns and composition at time of early loss of asthma control associate with severe asthma exacerbations.